A RESEARCH TOWARDS DETERMINING THE ECOTOURISM AND ECO-ENTREPRENEURSHIP POTENTIAL OF NAZARKÖY - Nişancı, Zehra Nuray; Haznedar, Helin Aslıhan (International Journal of Contemporary Economics and Administrative Sciences, 2018)
The aim of this research is to discover the ecotourism and eco-entrepreneurship potential of Nazarköy. Within this scope, the natural, cultural and geographic sources of the region and the perspective of local people on ecotourism and eco-entrepreneurship were focused. Nazarköy is a pretty settlement center located in Kemalpaşa district of İzmir, 4-5 km away from the district, 2 km.s inward from Torbalı highway, on the foothills of Nif Mountain. The means of living in the village with a population of approximately 400 people are cherries, tobacco and evil eye beads. The research is based on descriptive, heuristic, interview and observation. Within the scope of study, 30 people were face-to-face interviewed among the local people, it was endeavored to observe the local people and visitors by visiting the region and discovering the natural and cultural sources on-site. Participants in the interview give full support to the approach where sensitivity to the environment, necessity of awareness activities, management that does not harm the environment and natural environment are very important. As a result of the conducted studies, it was found out that Nazarköy has a rich potential for ecotourism activities. It was observed that the region has suitable natural sources for ecotourism activities such as festival tourism, mountain/rock climbing, trekking with horse, local handicrafts, nature photography, discovery of nature, bicycle tourism, camp/caravan tourism and scouting. Furthermore it can be stated that the existing business owning entrepreneurs and those individuals with potential to set up new businesses have an eco-entrepreneurial approach.